2018
DOI: 10.3390/ijms19113345
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Cripto-1 Suppresses Self-Renewal of Cancer Stem Cell Model

Abstract: Cripto-1 is a glycophosphatidylinositol (GPI) anchored signaling protein of epidermal growth factor (EGF)-Cripto-1-FRL1-Cryptic (CFC) family and plays a significant role in the early developmental stages and in the different types of cancer cells, epithelial to mesenchymal transition and tumor angiogenesis. Previously, we have developed cancer stem cells (miPS-LLCcm) from mouse iPSCs by culturing them in the presence of conditioned medium of Lewis Lung Carcinoma (LLC) cells for four weeks. Nodal and Cripto-1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…CD24, located in lipid rafts through its GPI anchor, is demonstrated to be found in high levels in exosomes isolated from ovarian cancer cells, compared to other tumor biomarkers such as CA-125, EGFR and MUC18 ( 30 ). Since Cripto-1 has been reported as a cell surface GPI-linked glycoprotein ( 31 ), this study tested whether it can be found in exosomes. Cripto-1 was found in exosomes from the culture medium of PHCCA cell lines and the peripheral blood of mice implanted PHCCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD24, located in lipid rafts through its GPI anchor, is demonstrated to be found in high levels in exosomes isolated from ovarian cancer cells, compared to other tumor biomarkers such as CA-125, EGFR and MUC18 ( 30 ). Since Cripto-1 has been reported as a cell surface GPI-linked glycoprotein ( 31 ), this study tested whether it can be found in exosomes. Cripto-1 was found in exosomes from the culture medium of PHCCA cell lines and the peripheral blood of mice implanted PHCCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…The phages with the affinity to recombinant soluble human CR-1 protein (rshCR-1) [ 28 ] were concentrated by bio-panning. After three rounds of bio-panning, phage clones exhibiting the affinity to rshCR-1 were isolated.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, the results obtained by Watanabe and colleagues were replicated in esophageal squamous cell carcinoma (ESCC) cell lines [67]. Mouse-induced CSCs exposed to soluble CR-1, which compete with endogenous CR-1 for Nodal signaling, display a reduction in the self-renewal ability, as well as a decrease in the ability to migrate and form spheroids in vitro [68]. In a recent study, it was demonstrated that the expression of CR-1 in human CSCs from colorectal cancers (CRC) spheroids originated from patients is not stationary.…”
Section: The Role Of Nodal and Cripto-1 In Cancer Stem Cellsmentioning
confidence: 95%